2020
DOI: 10.3390/antiox9111133
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Action of Antidiabetic Drugs on the Free Radical Production by the Rod Outer Segment Ectopic Aerobic Metabolism

Abstract: Rod outer segments (OS) express the FoF1-ATP synthase and the respiratory chain, conducting an ectopic aerobic metabolism that produces free radicals in vitro. Diabetic retinopathy, a leading cause of vision loss, is associated with oxidative stress in the outer retina. Since metformin and glibenclamide, two anti-type 2 diabetes drugs, target the respiratory complexes, we studied the effect of these two drugs, individually or in association, on the free radical production in purified bovine rod OS. ATP synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…In addition, we showed that SUR1-TRPM4 and SUR1-Kir 6.2 co-localized in the primate macula that is enriched in cone photoreceptors, showing a potential direct effect of glibenclamide on photoreceptors [21]. This observation is supported by a recent study showing that glibenclamide regulates photoreceptor metabolism and inhibits the production of oxygen reactive species induced by the exposure of the photoreceptor's outer segment to light [22]. Altogether, these results indicate that sulfonylureas could exert direct neuroprotective effects on the diabetes-induced retinal neurodegeneration.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, we showed that SUR1-TRPM4 and SUR1-Kir 6.2 co-localized in the primate macula that is enriched in cone photoreceptors, showing a potential direct effect of glibenclamide on photoreceptors [21]. This observation is supported by a recent study showing that glibenclamide regulates photoreceptor metabolism and inhibits the production of oxygen reactive species induced by the exposure of the photoreceptor's outer segment to light [22]. Altogether, these results indicate that sulfonylureas could exert direct neuroprotective effects on the diabetes-induced retinal neurodegeneration.…”
Section: Introductionsupporting
confidence: 78%
“…Recently, Ravera et al used in vitro experiments to show that glibenclamide could interfere with the respiratory complex of rods by targeting the mitochondrial respiratory complexes I, II, and III and inhibiting the oxidative metabolism and oxidative stress. They also showed a synergistic effect of glibenclamide with metformin on reducing the production of oxygen reactive species [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the retina, TUDCA has been shown to act on multiple cell types, through anti-apoptotic, anti-inflammatory, and antioxidant mechanisms [ 26 ]. For example, TUDCA has been reported to increase phagocytosis [ 49 ] and reduce oxidative stress in rod outer segments [ 50 ]. The rod outer segments are the sites of reactive oxygen species production and accumulation, which have been implicated as one of the pathogenic mechanisms in DR [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Purified bovine POS were prepared as previously described [23]. ARPE-19 cells, previously treated with miRNA mimic or miRNA inhibitor, were pulsed with 8 µg POS in CTR or HG medium; two batches of control cells (CTR and HG) were incubated in DMEM w/o POS.…”
Section: Phagocytosis Assaysmentioning
confidence: 99%